Prognostic impact of a compartment-specific angiogenic marker profile in patients with pancreatic cancer - Kahlert, Christoph; Fiala, Maria; Musso, Gabriel; Halama, Niels; Keim, Sophia; Mazzone, Massimiliano; Lasitschka, Felix; Pecqueux, Mathieu; Klupp, Fee; Schmidt, Thomas; Rahbari, Nuh Nabi; Schölch, Sebastian; et al. (OncoTarget, 2014)
Pancreatic cancer consists of a heterogenous bulk of tumor cells and stroma cells which contribute to tumor progression by releasing angiogenic factors. Those factors can be detected as circulating serum factors. We performed a compartmentspecific analysis of tumor-derived and stroma-derived angiogenic factors to identify biomarkers and molecular targets for the treatment of pancreatic cancer.
Gesehen am 16.10.2020